CB2 Agonist GW842166x Protected against 6-OHDA-Induced Anxiogenic- and Depressive-Related Behaviors in Mice - Xiaojie Liu; Hao Yu; Bixuan Chen; Vladislav Friedman; Lianwei Mu; Thomas J. Kelly; Gonzalo Ruiz-Pérez; Li Zhao; Xiaowen Bai; Cecilia J. Hillard; Qing-song Liu (Biomedicines, 2022)
In addition to motor dysfunction, patients with Parkinson’s disease (PD) are often affected by neuropsychiatric disorders, such as anxiety and depression. In animal models, activation of the endocannabinoid (eCB) system produces anxiolytic and antidepressant-like behavioral effects. CB2 agonists have demonstrated neuroprotective effects against neurotoxin-induced dopamine neuron loss and deficits in motor function. However, it remains unknown whether CB2 agonism ameliorates anxiogenic- and depressive-like behaviors in PD models. Here, we report that the selective CB2 agonist GW842166x exerted neuroprotective effects against 6-hydroxydopamine (6-OHDA)-induced loss of dopaminergic terminals and dopamine release in the striatum, which were blocked by the CB2 antagonist AM630. We found that 6-OHDA-treated mice exhibited anxiogenic- and depressive-like behaviors in the open-field, sucrose preference, novelty-suppressed feeding, marble burying, and forced swim tests but did not show significant changes in the elevated plus-maze and light–dark box test. GW842166x treatments ameliorated 6-OHDA-induced anxiogenic- and depressive-like behaviors, but the effects were blocked by CB2 antagonism, suggesting a CB2-dependent mechanism. These results suggest that the CB2 agonist GW842166x not only reduces 6-OHDA-induced motor function deficits but also anxiogenic- and depressive-like behaviors in 6-OHDA mouse models of PD.